Cultural Adaptation and Psychometric Properties of Long-term Conditions Questionnaire for Patients With Diabetes Mellitus - Raziyeh Iloonkashkooli; Zahra Hadian Shirazi; Mitra Soltanian; Giti Setoodeh; Marziyeh Momennasab (Journal of Client-centered Nursing Care)
Background: To evaluate the improved outcomes for individuals with long-term conditions (LTCs), health care providers need a valid and reliable tool for assessing patients with one or more LTCs. Despite the availability of the long-term conditions questionnaire (LTCQ), its Persian version is not currently available. Given the increasing prevalence of diabetes in Iran, psychometric evaluation of LTCQ seems necessary. Therefore, this study was conducted to ensure the reliability and validity of the Persian version of this questionnaire to assess LTCs in the Iranian diabetic population. Methods: We performed a methodological study. After the translation process, the face and content validity of the instrument were evaluated through qualitative and quantitative methods. To evaluate the construct validity of the Persian version of the questionnaire, a cross-sectional study was conducted among 205 patients with diabetes mellitus (DM) admitted to the outpatient clinic of a hospital in Shiraz City, Iran, utilizing exploratory and confirmatory factor analysis (EFA and CFA, respectively). The Cronbach α method and intraclass correlation coefficient were used to measure internal consistency and test re-test reliability, respectively. SPSS software, version 23 and AMOS version 24 were used for statistical analysis. Results: The findings of maximum likelihood by the varimax rotation and CFA showed that the Persian version of LTCQ has 3 factors: 1) Adaptation to illness, 2) Independence, and 3) Self- management. Regarding the EFA, two questions were removed. Considering the CFA, all questions had factor loadings exceeding 0.3, and the goodness-of-fit indices were deemed satisfactory (χ2/df=1.9). The root mean square error of approximation was 0.056, the comparative fit index was 0.93, and the parsimony goodness-of-fit index was 0.78. The indices of internal consistency and reliability for the LTCQ were close to the acceptable range (the Cronbach α: 0.72–0.85 and intraclass correlation coefficient: 0.78–0.95). Finally, the LTCQ with 18 questions was approved. Conclusion: The findings suggest that the Persian version of LTCQ is a valid and reliable tool for assessing the impact of illness experienced by Iranian patients with diabetes mellitus.